CENP-V is required for proper chromosome segregation through interaction with spindle microtubules in mouse oocytes - Dalileh Nabi (Nature Portfolio, 2021)
Chromosome segregation is essential to avoid aneuploidy, yet in mammalian oocytes it progressively fails in an age-dependent manner. Here the authors identify CENP-V as a microtubule binding and bundling protein crucial to faithful oocyte meiosis, and present Cenp-V−/− oocytes as revealing age-dependent weakening of the spindle assembly checkpoint.